How well do psychologists' research methods equip them to identify the impacts of climate change on behaviour? : a methodological investigation with particular reference to the effects of temperature on violent behaviour : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Albany, New Zealand - Williams, Matthew Neil (Massey University, 2015)
The Earth’s temperature is rising, and it is extremely likely that human activities are primarily to blame (IPCC, 2013b). A changing climate could have serious consequences for human behaviour and psychological functioning. Research concerned with the psychological impacts of climate change is challenging, however, given the paucity of data showing how human behaviour has responded to sustained climate changes in the past. In this thesis, I critique the suitability of psychologists’ mainstream methodological strategies for engaging in research concerned with the impacts of climate change. In doing so, I draw heavily on a specific “testbed” of psychological research relevant to climate change: Research concerned with the impact of temperature on the incidence of intra- and interpersonal violence. In identifying methodological problems I draw both on published literature as well as an empirical engagement in research in this area. The empirical component constitutes an analysis of the relationship between temperature and the incidence of assault, suicide, and self-harm resulting in hospitalisation in New Zealand. In this analysis I found that irregular dayto- day variation in temperature had a positive relationship with all three forms of violence. However, there was less evidence that more sustained (seasonal or geographical) differences in temperature led to increased violence, making it difficult to predict the effects of sustained increases in temperature in the future. In the methodological critique section of this thesis, I point out several methodological problems that may hamper psychologists’ capacity to produce effective and useful research concerned with the impacts of climate change. These problems include the use of measurement and analysis strategies that limit our ability to convey the sizes of effects; the use of theories and analyses that limit our ability to make predictions; and the inadequate reporting of uncertainty. Finally, I recommend that psychologists studying climate change impacts should consider using categorisations of behaviour rather than psychometric scales that lack clear units of measurement; use statistics that effectively communicate effect size; apply theories that facilitate prediction-making; carefully take into account the role of time when generating predictions; and account for multiple sources of uncertainty that affect the confidence of our conclusions.
Listed in 2015 Dean's List of Exceptional Theses
Keywords: Climatic changes; Temperature; Psychological aspects; Violence; Environmental psychology; Dean's List of Exceptional Theses